Leather bracelets : 33 step-by-step instructions for leather cuffs, bracelets, and bangles with knots, beads, buttons and charms /: 33 step-by-step instructions for leather cuffs, bracelets, and bangles with knots, beads, buttons and charms. (2017) - Vogue-Sha, Nihon
No abstract available